2020
DOI: 10.1111/1759-7714.13754
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implication of minimal presence of solid or micropapillary subtype in early‐stage lung adenocarcinoma

Abstract: Background: We investigated the clinical features and surgical outcomes of lung adenocarcinoma with minimal solid or micropapillary (S/MP) components, with a focus on stage IA. Methods: We enrolled 506 patients with lung adenocarcinoma who underwent curative resection in this study. Clinical features and surgical outcomes were compared between the groups with and without the S/MP subtype (S/MP+ and S/MP−, respectively), and between the group with an S/MP proportion of ≤5% (S/MP5) and the S/MP−. Results: The S/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…In our retrospective cohort, the clinical features of each patient were systematically analyzed; 717 (11.17%) patients were confirmed to have a micropapillary component, and OLNM was observed in 20.13% of patients with an NP-MCP of lung adenocarcinoma measuring ≤ 3 cm. Our data demonstrated that tumor size, young age of onset, and solidand micropapillary-components were independent risk factors for OLNM, which is consistent with previous studies (21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 92%
“…In our retrospective cohort, the clinical features of each patient were systematically analyzed; 717 (11.17%) patients were confirmed to have a micropapillary component, and OLNM was observed in 20.13% of patients with an NP-MCP of lung adenocarcinoma measuring ≤ 3 cm. Our data demonstrated that tumor size, young age of onset, and solidand micropapillary-components were independent risk factors for OLNM, which is consistent with previous studies (21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 92%
“…According to the new pathological classification of lung adenocarcinoma proposed by IASLC/ATS/ERS, the patients with micropapillary and solid subtypes were considered to have poor prognosis. Several studies have reported that micropapillary/solid subtypes, including predominant and non‐predominant patterns, were associated with poor prognosis 4–7,9–12 . Lung adenocarcinomas are usually heterogeneous and contain a mixture of multiple subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Since a new histological classification of LUAD was proposed by IASLC/ATS/ERS, the impact of micropapillary or solid components on the survival of early lung cancer had attracted more attention. According to 384 patients with stage I lung adenocarcinoma, Choi et al 9 found that the presence or absence of micropapillary/solid patterns had a greater advantage over the stage IA/IB classification in distinguishing prognosis, indicating that the micropapillary/solid components may be a preferable prognostic factor compared with tumor size in stage I LUAD. Due to the importance of micropapillary and solid components in affecting the survival of patients with LUAD, the combination of two components is necessary to comprehensively evaluate the prognosis of patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicopathological characteristics including age, sex, tumor size, pathological type, tumor differentiation, adenocarcinoma subtype, and TNM stages were collected. According to the degree of invasion and adenocarcinoma subtype, patients were divided into two groups (Low Risk Group: AIS, MIA, lepidic, and acinar; High Risk Group: mucinous, micropapillary, and solid) ( 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%